Synthesis and Avidin Binding of Ruthenium Complexes Functionalized with a Light‐Cleavable Free Biotin Moiety. Issue 37 (20th August 2018) - Siewert, Bianka; Langerman, Michiel; Pannwitz, Andrea; Bonnet, Sylvestre
Abstract : In this work the synthesis, photochemistry, and streptavidin interaction of new [Ru(tpy)(bpy)(SRR′)](PF6 )2 complexes where the R′ group contains a free biotin ligand, are described. Two different ligands SRR′ were investigated: An asymmetric ligand1 where the Ru‐bound thioether is a N ‐acetylmethionine moiety linked to the free biotin fragment via a triethylene glycol spacer and a symmetrical ligand2 containing two identical biotin moieties. The coordination of these two ligands to the precursor [Ru(tpy)(bpy)Cl]Cl was studied in water at 80 °C. In such conditions the coordination of the asymmetric ligand1 occurred under thermodynamic control. After the reaction, a mononuclear and a binuclear complex were isolated. In the mononuclear complex, the ratio of methionine‐ [6 ](PF6 )2 vs. biotin‐bound [7 ](PF6 )2 regioisomer was 5.3 and the free biotin fragment of [6 ](PF6 )2 allowed to purify it from its isomer [7 ](PF6 )2 at small scales using avidin affinity chromatography. Coordination of the symmetrical ligand2 afforded [Ru(tpy)(bpy)(2 )](PF6 )2 [8 ](PF6 )2 in synthetically useful scales (100 mg), good yield (82 %), and without traces of the binuclear impurity. In this complex, one of the biotin remains free whereas the second one is coordinated to ruthenium. Photochemical release of ligand2 from [8 ](PF6 )2 occurred upon blue light irradiation (465 nm) with a photosubstitution quantum yield of 0.011 that was independent of the binding of streptavidin to the free biotin ligand. Abstract : A new synthetic strategy is presented for preparing photoactivated chemotherapeutic ruthenium compounds functionalized with a free biotin group. The free biotin fragment, which is bound to ruthenium via a thermally stable Ru–S bond, can still bind to streptavidin. Blue light irradiation resulted in the cleavage of the biotin‐bearing protecting ligand, thus liberating the ruthenium aqua compound.